Digit ratio (2D:4D) and performance of Chinese elite archers - Wu, J.; Liu, X.; Wang, Y.; Zhang, Y.; Fan, Y. (Journal of Men`s Health, 2022)
Background: Previous studies have found a correlation between digit ratio (2D:4D) and performance in sporting events which require physical competence. Such correlation, however, has not been well studied in technique-oriented sports. This study explored the correlation between 2D:4D and sporting performance of Chinese elite archers. Also it provides some references for sports research in other fields. Methods: We conducted the study with 31 Chinese elite archers (15 males and 16 females) preparing for the 2020 Tokyo Olympic Games and collected their 2D:4D ratios by measuring their index and ring fingers. The study also asked them to take physical fitness tests including push-ups, decline sit-ups, half-squat and a 4000-meter run, and obtained their results in former ranking tournaments and Olympic elimination series. The study recorded every entry of data in a "mean ± standard deviation" (M ± SD) format and processed them in SPSS 24.0 to produce One-Way ANOVA and Pearson correlations. Results: Our study found no significant difference between varied sporting levels in the left 2D:4D, and between world-class and national-level archers in the right 2D:4D (p > 0.05), yet a significant one between left-right 2D:4D of world-class, national-level, and level-1 archers (p < 0.01). We also found no significant correlation between the left 2D:4D and specific physical fitness test results, and between those archers` results. Similarly, there was a significant negative correlation between the right 2D:4D and specific test results (p < 0.05), and a strong negative correlation between that and results of ranking tournaments (p < 0.01) and Olympic elimination series (p < 0.01). Conclusions: Chinese elite archers with lower right 2D:4D are of better physical fitness and enhanced sport performance. Hence, the right 2D:4D may act as a critical indicator in selecting excellent archers.